Sterigmatocystin in foodstuffs and feed: aspects to consider - Viegas, Carla (2018)
Sterigmatocystin (STC) is a possible human carcinogen (2B) according to the International Agency for Research on Cancer classification and has been associated with the immunotoxic and immunomodulatory activity, together with mutagenic effects. It might be found in numerous substrates, from foods and feeds to chronically damp building materials and indoor dust. Although the European Food Safety Authority concluded that the exposure to STC to be of low concern for public health, reinforces the need of data concerning exposure of European citizens. Climate change can represent an increased risk of exposure to STC since it is a crucial factor for agro-ecosystem powering fungal colonization and mycotoxin production This aspect can represent an increased risk for European countries with temperate climates and it was already reported by the scientific community.